The potential of thermally expanded graphite in oil sorption applications - Elbidi, Moammar; Mohd Salleh, Mohamad Amran; Abdul Rashid, Suraya; Mukhtar Gunam Resul, Mohamed Faiz (Royal Society of Chemistry, 2024)
An oil spill occurs when liquid petroleum hydrocarbons are released into the environment, whether accidentally or intentionally, in substantial quantities. The impact of an oil spill on the ecosystem is significant and should not be underestimated. Various techniques are employed to address oil spills, including mechanical, physical, biological, and physicochemical methods. Among these techniques, adsorption is considered the most suitable approach. Adsorption is promising due to its simplicity, ease of use, high removal capacity, and rapid pollutant removal. An excellent adsorbent material exhibits unique characteristics that enhance its efficacy in liquid adsorption. Sorbents are categorized into synthetic and natural types. Porous carbon materials, especially expanded graphite, are widely utilized in wastewater treatment due to their micropores and exceptional adsorption capacity. The distinctive properties of expanded graphite, including its low density, high porosity, and electrical conductivity, have garnered significant global attention for various potential applications. In essence, expanded graphite offers a powerful and practical approach to oil spill cleanup due to its efficient oil adsorption, selective targeting, ease of use, and potential reusability. This review article summarizes the preparation techniques, structure, and properties of expanded graphite. It also delves into recent advancements in using expanded graphite for oil spill cleanup. The article concludes by outlining potential future directions in this field and discussing the commercial viability of some of these techniques.